Aortopulmonary window in adulthood: Surviving at 22 years without intervention or pulmonary vascular disease - İsa Öner Yüksel; Erkan Köklü; Sakir Arslan; Cagin Mustafa Ureyen; Selcuk Kucukseymen (KARE Publishing, 2016)
Summary- Aortopulmonary window is a rare anomaly, a communication between the ascending aorta and the main pulmonary artery. Prognosis in the absence of correction is poor, with mortality of around 40% in the first year of life. A case of aortopulmonary window without pulmonary vascular disease in adulthood is described in the present report.